Experiences of staff working in a mental health trust during the COVID-19 pandemic and appraisal of staff support services. Issue 2 (1st February 2022) - Jones, Abbeygail; Zhang, Shuo; Woodburn, Amy; Dorrington, Sarah; Beck, Alison; Winter, Helen
Abstract : Purpose: The health and well-being of healthcare staff came into focus during the coronavirus disease-2019 (COVID-19) pandemic as already strained workforces responded to new and additional challenges. Organisational support services made efforts to adapt staff support provision. However, most literature and recommendations are centred on surveys of medical and clinical staff. The present study included staff across clinical and non-clinical workforces within a mental health trust over the course of the COVID-19 pandemic to date, and aimed to understand workforces' access to and experiences of organisational support. Design/methodology/approach: The current study was a qualitative one using convenience and purposive sampling. Semi-structured individual and group interviews were conducted using a topic guide. Reflexive thematic analysis was used in a phenomenological framework to analyse data. Findings: 35 staff, broadly representative of the trust workforce, were recruited. Six global themes summarised the experiences of staff in relation to work practices, personal well-being and support access over the first year of the COVID-19 pandemic: COVID-19 disease, interpersonal relationships, individual considerations, change, working environment and support. Practical implications: The findings from the study have implications for organisational support provisions for healthcare workers and the dissemination of these services. Originality/value: Acknowledging the multi-various experiences of different workforces within National Healthcare Service organisations and how these change over time will facilitate innovative changes to staff support provision.